What Are the Influences of Entertaining eWOM on Social Media-an Empirical Study on the Use of Brand-related Hashtags on Weibo and Customer Engagement - Zhao, Lisa (2019)
The influences of eWOM has been extensively investigated due to its beneficial marketing outcomes on product purchase intention, brand perception, CE (customer engagement) etc., which has been largely examined and approved in previous literature. However, preceding studies mainly focus on “legacy” forms of eWOM involving consumer’s statements through product ratings and reviews (Lamberton and Stephen 2016), thus fail to keep pace with the prevalent marketing practice on new forms of eWOM such as Hashtag campaigns on social media. Additionally, entertaining content has long been considered as a silent antecedence of CE in eWOM by many researchers, given the lack of study on such content generated by users, this research combined the two gaps and concerns the influences of such entertaining eWOM on CE in a specific context on social media in an attempt to provide marketing implications to practitioners.